Purchasing Behavior and Customers’ Response to the Intrinsic and Extrinsic Factors of the Pharmaceutical Products in Bangladesh - Bhuiya, N. M. Mahmudul Alam (International Journal of Pharmaceutical & Biological Archive, 2021)
The prime objective of the study is to assess the purchasing behavior of pharmaceutical products among customers in Bangladesh and their response to the diverse range of intrinsic and extrinsic factors of the pharmaceutical products. Multi-item measures were utilized to collect information through a questionnaire-based survey to evaluate respondents’ attitudes toward the distinctive characteristics of the pharmaceutical products. Among 410 participants, 266 respondents were assessed who purchase pharmaceutical products at least once monthly in last 1 year and answered all the questions properly. Shopkeepers’ suggestions, product presentation, packaging material, product visibility, and packaging quality were singled out, which significantly impacted the purchasing behavior and brand evaluation. Significant gender differences were also observed in purchasing pharmaceutical products influenced by doctors’ prescriptions (χ2 = 10.278, P = 0.016) and evaluating brand based on bitterness of the taste (χ2= 6.792, P = 0.034). The association of the academic level of the customers was also observed in the most deciding factor in purchasing pharmaceutical products (χ2 = 27.039, P = 0.000) and evaluation of the brand based on company image (χ2 = 4.076, P =0.043), color of the liquid dosage form (χ2 = 8.562, P = 0.014), taste difference (χ2 = 11.346, P = 0.023), and bitterness of the liquid dosage form (χ2 = 7.245, P = 0.027). Regardless of gender and education level, the majority preferred transparent, dual packaging and strips of solid dosage forms that are marked with the days of a week.